EXTH-06. PRE-INFUSION METABOLIC MODULATION OF CAR-T CELLS PROMOTES THE RESISTANCE TO THE SUPPRESSIVE EFFECTS OF HYPOXIA AND ENHANCES ANTI-TUMOR EFFECTS AGAINST INTRACEREBRAL GLIOMAS. (14th November 2022) - Hatae, Ryusuke; Kyewalabye, Keith; Yamamichi, Akane; Chen, Tiffany; Chuntova, Pavlina; Okada, Hideho
Abstract: Effective immunotherapy for glioma has not yet been established. We have found the energy metabolic status of immune cells within the tumor microenvironment is remarkably different between intracerebral and extracranial tumors. In mice bearing intracerebral SB28-EGFRvIII gliomas with intravenous infusion of EGFR vIII-targeting CAR-T cells, we found that mitochondrial markers in tumor-infiltrating T cells were down-regulated compared to those in splenic T cells. Therefore, we hypothesized that the treatment of CAR-T cells with a metabolic regulator that activates mitochondria before infusion would improve the therapeutic effect of CAR-T cells. Using a hypoxic incubator to mimic the tumor microenvironment of brain tumors, we screened drugs that would improve the metabolic state of CAR-T cells and sustain their anti-tumor effect. We have found that, although the mammalian target of rapamycin (mTOR) inhibitor rapamycin and AMP-activated protein kinase (AMPK) activator metformin are ineffective when administered as single drugs, the combined use of these drugs (met+rap) prolongs the anti-glioma effect of CAR-T cells under hypoxic conditions. A single intravenous infusion of CAR-T cells that were pre-treated with met+rap significantly prolonged the survival of mice bearing intracerebral SB28-EGRFvIII tumors compared with CAR-T cells without the pre-infusion treatment. Met+rap-treated CAR-T cells infiltrated the intracerebral tumor more effectively and maintained their functions better than the control CAR-T cells, suggesting that the met+rap treatment conferred CAR-T cells with abilities to traffick and function in the severe microenvironment of brain tumors. Importantly, because the CAR-T cells were pre-treated with the drugs during the in vitro expansion only but without drug administrations in vivo, this strategy would circumvent any toxicity associated with in vivo treatments with the same drugs. These data suggest that the treatment of CAR-T cells during the in vitro expansion with the two drugs may improve the efficacy of CAR-T cell therapy for brain tumors.